1997
DOI: 10.1159/000057350
|View full text |Cite
|
Sign up to set email alerts
|

Protein Metabolism in Acute Renal Failure

Abstract: The hallmark of metabolic alterations in acute renal failure (ARF) is accelerated protein breakdown which, unfortunately, cannot be suppressed effectively by provision of exogenous nutritional substrates. Causes of excessive protein catabolism are manifold and present a combination of unspecific mechanisms induced by the acute disease process and underlying illness or associated complications, effects induced by the acute loss of renal function and, finally, the type and intensity of renal replacement therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Furthermore, excessive urinary excretion of albumin in nephritic states is thought to arise from structural changes in capillary wall permeability (39). Accelerated protein breakdown is a hallmark of metabolic alterations; thus, protein catabolism has been attributed to the acute disease process, uremic toxins, inflammatory mediators, metabolic acidosis, hormonal imbalance, and insulin resistance (39,40). The present results demonstrated that the serum level of albumin in diabetic control rats decreased compared to normal rats, while oral administration of the BuOH fraction to diabetic rats slightly increased the serum level of albumin, indicating that albumin loss induced by urinary elimination under diabetic conditions was attenuated by oral administration of the BuOH fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive urinary excretion of albumin in nephritic states is thought to arise from structural changes in capillary wall permeability (39). Accelerated protein breakdown is a hallmark of metabolic alterations; thus, protein catabolism has been attributed to the acute disease process, uremic toxins, inflammatory mediators, metabolic acidosis, hormonal imbalance, and insulin resistance (39,40). The present results demonstrated that the serum level of albumin in diabetic control rats decreased compared to normal rats, while oral administration of the BuOH fraction to diabetic rats slightly increased the serum level of albumin, indicating that albumin loss induced by urinary elimination under diabetic conditions was attenuated by oral administration of the BuOH fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin level is one of the indicators of nutritional status that has been demonstrated as a mortality (20,21). Acute renal failure is one of the conditions that induce protein catabolism due to uremic toxins, infl ammatory mediators, metabolic acidosis, and hormonal imbalance (22). In addition, decreased serum albumin is associated with infl ammatory conditions because it is one of the negative acute phase reactive proteins (23).…”
Section: The Diagnosis N (%)mentioning
confidence: 99%
“…It has been suggested [4] that in order to achieve a positive nitrogen balance in critically ill patients with renal dysfunction hormonal manipulation is needed in the form of either growth hormone (GH) or insulin-like growth factor-I (IGF-I). Both these agents have a significant anabolic effect.…”
Section: Hormonal Impact Of Crrt and Hormonal Manipulationmentioning
confidence: 99%